Numerical study of adiabatic two-phase flow patterns in vertical rectangular narrow channels. (5th January 2017) - Wei, Lie; Pan, Liang-Ming; Zhao, Yan-Ming; Ren, Quan-Yao; Zhang, Wen-Zhi
Highlights: Adiabatic two-phase flow pattern map in upward rectangular channel was simulated. The range of annular flow in small channel is larger, while the one of slug and bubbly flow are smaller. With the reducing gap size, the flow pattern transition shifts to left. Simple inlet condition is testified applicably to simulate flow patterns. CFD method is a feasible way to draw the two-phase flow patterns map. Abstract: The current paper investigates an upward two-phase flow of air-water mixture in vertical narrow rectangular channels with two different cross-sectional dimensions of 25 × 5 mm and 25 × 2 mm respectively by using VOF (Volume of Fluid) model. To facilitate the simulations of different flow patterns, a simple and practical inlet condition, which is validated by experimental results, is employed. In the VOF model, the inlet condition will make the gas phase to be air layers, and due to the entrainment effect, the layers would coalescent and break up to small bubbles. The simulation results reveal that the main flow patterns of the two-phase flow in narrow channels are bubbly flow, slug flow, churn-turbulent flow and annular flow, and the void fraction distributions of those flow patterns are quite different. The void fraction of bubbly flow is below 0.3, which is consistent with published literatures. As the Taylor bubbles are located at the center of the flow channel and the slug flow is intermittent, the void fraction of slug flow is more evenly distributed in the center. The flow pattern map has been drafted under various air–water superficial velocities. The central region of the annular flow is gas core entrained liquid droplets, thus the void fraction is almost constant in the central region. The two-phase flow pattern map of a vertical rectangular channel shows that the range of annular flow in the channel is larger, while the scopes of slug flow and bubbly flow in the channel are smaller in comparison with the flow pattern map of tube. In addition, the transitional boundaries between flow patterns occur at smaller gas velocity than those in the tube. While compared the 2 mm gap rectangular channel with the 5 mm ones, it is found that with the gap size reducing, the flow pattern transition boundary shifts to the left.